THE DYNAMIC OF CODE-SWITCHING IN BILINGUAL ADOLESCENTS (Ta'limning zamonaviy transformatsiyasi, 2024)
Abstract. This paper examines the sociolinguistic factors that trigger CS among English-Russian bilingual teenagers. Using a qualitative approach, we examine conversational data from semi-structured interviews to discuss the interdependence of CS with social setting, interlocutor, topic, and identity. Our findings indicate a complex interplay of factors shaping the CS practices that underlines both the strategic and communicative competence of these bilingual speakers and points at the role of CS in identity negotiation.